Analysis of the Impact of the Existence of Kuala Namu Airport on the Income of Culinary Business MSMEs in Batang Kuis - Nurul Tri Amanda; Isnaini Harahap; Muhammad Lathief Ilhamy Nasution (Jurnal Riset Ekonomi Manajemen (REKOMEN), 2024)
The developments that take place in the Kuala Namu Airport area contribute to regional growth. Observations revealed that their income grew dramatically with the establishment of Kuala Namu airport. The purpose of this study is to assess the impact of the Kuala Namu Airport on culinary business MSMEs in Batang Kuis. This study combines field research with a qualitative descriptive method. This research data was gathered using observation techniques, interviews, and documentation studies. Data was evaluated using data reduction, data presentation, and data verification techniques, as well as SWOT analysis. The research findings explain that the existence of Kuala Namu Airport has had a positive impact on people's income, where before the airport, the average income of culinary business MSMEs in Batang Kuis was only IDR 3,645,000, and after the airport was built, the average income of people increased to IDR 10,447,500, with a 100% increase. Knowing your strengths and weaknesses, as well as potential possibilities and threats. Culinary Business MSMEs in Batang Kuis can be more prepared to use and optimize both the potential and opportunities that exist in the area, as well as to improve existing shortcomings and be ready to confront varied competitors or threats that occur.